2022
DOI: 10.9734/jpri/2022/v34i1b35784
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Determinants of Neonatal Mortality in Afar and Somalia Regions, Ethiopia

Abstract: Background: Children face the highest risk of dying in their first month of life. Ethiopia is one of the sub-Saharan countries with highest newborn deaths. Afar and Somalia regions in Ethiopia are among the regions with high death rates of newborn children. This study aimed to analyse and identify determinants of neonatal mortality in Afar and Somalia regions, Ethiopia.  Methods: This study used 2016 Ethiopian Demographic and Health Survey data for the analysis. The multivariable logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…Our study also revealed that infants born at health facilities were less likely to die before first birth day than infants born at home. This result is consistent with the previous studies 17 , 21 , 31 , 39 41 . This could be due to that babies born at health facilities may get better care during the delivery as it assisted by health professionals compared to those born at home.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study also revealed that infants born at health facilities were less likely to die before first birth day than infants born at home. This result is consistent with the previous studies 17 , 21 , 31 , 39 41 . This could be due to that babies born at health facilities may get better care during the delivery as it assisted by health professionals compared to those born at home.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, infants whose birth type was single were less likely to die before first birthday than infants whose birth type was multiple. This agrees with studies 11 , 17 , 21 , 31 , 42 , 45 50 . This could be because of that multiple births share foods and cares provided to them whereas the singletons use without sharing.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with prior studies [28,33,43,51]. Higher U5M rate was also associated with children of multiple births, which is consistent with the studies [8][9][10]32,39,48,52,53]. Lower U5M rate was associated with larger family size.…”
Section: Plos Onesupporting
confidence: 92%